The Law of Peoples: The Old and the New - Chris Naticchia (Journal of Moral Philosophy 2005; 2; 353, 2005)
John Rawls produced two versions of the law of peoples: an article, published in 1993, and a book, published in 1999. Both versions defend basic human rights as a minimum requirement of a just law of peoples. However, in an apparent effort to strengthen his defense of this requirement, the argument changed. This paper examines the apparent difficulties that forced the changes and maintains that they still do not succeed in justifying basic human rights. The source of the difficulty, I argue, is Rawls's reluctance to impose liberal values on nonliberal societies, and the imposition of such values, I suggest, is unavoidable if basic human rights are to be justified. Hence, if our best attempts to justify basic human rights ultimately show that appeals to liberal values are unavoidable, then we should regard such appeals as no more of an imposition than the expectation that all societies must protect basic human rights. Even more significantly, Arguments in support of basic human rights would also justify international efforts to advance further liberal reforms within nonliberal societies.